A Longitudinal Examination of Veterans Treatment Courts' Characteristics and Eligibility Criteria. (December 2016) - Timko, Christine; Flatley, Bessie; Tjemsland, Amanda; McGuire, Jim; Clark, Sean; Blue-Howells, Jessica; Blonigen, Daniel M.; Rosenthal, Joel; Finlay, Andrea
Although the number of Veterans Treatment Courts (VTCs) has been growing at a rapid rate, thus far, VTC components have not been standardized, due in part to a lack of empirical evidence on the extent to which components vary across VTCs nationwide and change over time. This study analyzed data collected by the Department of Veterans Affairs' Veterans Justice Program, on VTCs in 2012 ( n = 173 Courts), 2013 ( n = 266), and 2014 ( n =351 ), to describe Court characteristics, participant eligibility criteria, and Courts' mentoring component. Despite growth in VTC numbers, the survey found consistency over time in these aspects of VTCs. Regarding characteristics, the majority of Courts had jurisdiction at the county level. Across survey years, the range of means was 22–24 for veteran participant census, 10–14 for number of months spent in the Court for misdemeanors, and 18–19 for number of months spent in the Court for felonies. Eligibility requirements suggested openness to veterans of different backgrounds and status. Less than two thirds of Courts had the mentoring component; Courts with the mentoring component had a higher participant census and a longer duration of participants' time under Court supervision than Courts without this component. Existing mentoring programs were organized mainly by volunteers. VTCs' adherence to policies supportive of veterans may benefit from having paid mentor coordinators in order to further ensure this hallmark of VTCs.